Mineral Chemistry Studies on Pyroxenes in Fe Skarns in the West of Elazig (Turkey); Their Role in the Skarn Mineralization Process - Koprubasi, Necla; Kilic, Ayse Didem; Sasmaz, Ahmet (Mdpi, 2025)
This study presents the first detailed investigation of pyroxene zoning within polymetallic skarn zones of the Elazig region. Skarns develop along contacts between plutonic rocks (diorite and granite) and carbonate rocks, forming two main zones: endoskarn and exoskarn. Endoskarns exhibit clear mineralogical zoning, including pyroxene-garnet, pyroxene-scapolite, and epidote-garnet assemblages, while scapolite occurs in both endoskarn and exoskarn zones. Minor serpentinized olivine within endoskarns is attributed to localized magnesium enrichment due to partial assimilation of low-Mg magma by dolomitic marbles. Geochemical analyses reveal systematic variations in pyroxene composition related to ore type: Cu-Fe skarns show low Mn/Fe ratios (<0.1) and low Zn (similar to 200 ppm), Fe skarns have high Mn/Fe ratios (>0.2) and elevated Zn (>200 ppm), and W-bearing skarns display intermediate Mn/Fe ratios (similar to 0.15) with high Zn (>500 ppm). These findings highlight the value of pyroxene Mn/Fe ratios and Zn contents as indicators of hydrothermal fluid evolution and skarn-forming processes. Overall, this study provides the first evidence of oscillatory zoning in pyroxenes from polymetallic skarns in the region, demonstrating the interplay between magmatic differentiation and hydrothermal mineralization.
Keywords: Elazig magmatites; compositional zoned; pyroxenes; skarn mineral